Exploring Efl Students' Experiences of Self-Regulated Learning Strategy in Extensive Reading - Vici, Diajeng Nada; Saefullah, Hilmansyah; Miftakh, Fauzi Miftakh (Journal of Educational Sciences, 2025)
The decline in student literacy rates in Indonesia has prompted the adoption of extensive reading strategies with self-regulated learning (SRL) strategies to increase interest and independent reading skills. This case study aims to explore students' experiences using SRL strategies during extensive reading activities. Five high school students volunteered as participants, and data were collected through weekly journals and reading logs documenting the SRL phases (forethought, implementation, and self-reflection), as well as semi-structured interviews after the activity. The study findings indicate that SRL strategies help students choose appropriate learning strategies, improve time management skills, and facilitate the achievement of reading goals. Overall, participants reported positive benefits from using SRL, including improved English language skills and more effective learning management. The study's conclusions confirm that the application of SRL has proven relevant and beneficial in the context of extensive reading, providing practical implications that SRL-based literacy education can support increased interest and independent reading skills among high school students.